2020
DOI: 10.1001/jamaneurol.2020.1948
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Cryptogenic Stroke With Patent Foramen Ovale at Older Ages and Implications for Trials

Abstract: IMPORTANCE Patent foramen ovale (PFO) closure may prevent recurrent stroke after cryptogenic transient ischemic attack (TIA) or stroke (TIA/stroke) in patients aged 60 years or younger. Patent foramen ovale is associated with cryptogenic stroke in the older population, but risk of recurrence is unknown. Data on prognosis of patients receiving medical treatment at older ages (Ն60 years) are essential to justify trials of PFO closure. OBJECTIVE To examine the age-specific risk of recurrence in patients with cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…The ongoing Atrial Cardiopathy and Antithrombotic Drugs in Prevention After Cryptogenic Stroke (ARCADIA, NCT03192215) ( 101 ), Apixaban for Treatment of Embolic Stroke of Undetermined Source (ATTICUS, NCT02427126), and A Study on BMS-986177 (oral factor XIa inhibitor) for the Prevention of a Stroke in Patients Receiving Aspirin and Clopidogrel (AXIOMATIC-SSP, NCT03766581) trials will, hopefully, provide conclusive results to guide patient care. Likewise, in the Oxford Vascular Study, a large patent foramen ovale is present in 36% of patients with a cryptogenic stroke aged >60 years ( 119 ) and associated with a 2.5 times higher risk of recurrent ischemic stroke ( 120 ), thus suggesting it might be worth trialing PFO closure or anticoagulation in elderly patients with a large PFO. However, the causal relationship between the PFO and the recurrent stroke was not formally established and the prevalence of ipsilateral non-stenotic carotid plaque not reported.…”
Section: Challenges Of Secondary Stroke Preventionmentioning
confidence: 99%
“…The ongoing Atrial Cardiopathy and Antithrombotic Drugs in Prevention After Cryptogenic Stroke (ARCADIA, NCT03192215) ( 101 ), Apixaban for Treatment of Embolic Stroke of Undetermined Source (ATTICUS, NCT02427126), and A Study on BMS-986177 (oral factor XIa inhibitor) for the Prevention of a Stroke in Patients Receiving Aspirin and Clopidogrel (AXIOMATIC-SSP, NCT03766581) trials will, hopefully, provide conclusive results to guide patient care. Likewise, in the Oxford Vascular Study, a large patent foramen ovale is present in 36% of patients with a cryptogenic stroke aged >60 years ( 119 ) and associated with a 2.5 times higher risk of recurrent ischemic stroke ( 120 ), thus suggesting it might be worth trialing PFO closure or anticoagulation in elderly patients with a large PFO. However, the causal relationship between the PFO and the recurrent stroke was not formally established and the prevalence of ipsilateral non-stenotic carotid plaque not reported.…”
Section: Challenges Of Secondary Stroke Preventionmentioning
confidence: 99%
“…These associated findings are crucial in risk stratification of PFO in cryptogenic AIS and help in further secondary stroke prevention strategies. [ 38 47 48 ] Recent clinical trials reported that cryptogenic AIS patients with PFO along with structural abnormalities such as ASA are at higher risk of paradoxical emboli and might benefit from PFO closure resulting in lower recurrence rate. [ 39 ] Our study confirms that TEE was able to detect ASA associated with PFO in 2.3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is in recognition that the annualized risk reduction is relatively low, at roughly 0.6%, but that the cumulative risk over time for a relatively young patient can be viewed as substantial. It has been pointed out that TIA and stroke can be seen in older subjects in association with TIA [ 63 , 64 ] and that the pathological mechanism might actually be enhanced in this older population, related to higher incidence of venous thrombosis with age, increased pulmonary pathology which could increase right-sided heart pressure and facilitate a right-to-left shunt as well the potential for an increase in PFO size with age [ 65 ]. These authors report on a pooled analysis of four studies of recurrent stroke, in subjects with and without PFO, and identified an enhanced risk of stroke recurrence with PFO only at age ≥65 years with an odds ratio of 2.5.…”
Section: Stroke Risk and Patent Foramen Ovale (Pfo)mentioning
confidence: 99%